Analysis of Benefit-Cost Ratio in the Utilization of BIM for the Construction Project of the Mobile Brigade Corps (MAKO Brimob) Building and the State Police School (SPN) of North Sulawesi Police - Azis, Aminudin; Rafsanjani, Hardhi; Laksono, Riyadi Dwi; Fitriyani, Nevia (Journal of Civil Engineering, 2024)
PT Buana Enjiniring Konsultan is one of the engineering consulting firms in Indonesia. In addition to being active in the engineering field, PT Buana Enjiniring Konsultan has also ventured into digital engineering by providing Building Information Modeling (BIM) services. As a subsidiary of PT Brantas Abipraya, PT Buana Enjiniring Konsultan is committed to ensuring that the BIM products provided are of high quality and meet construction industry standards. By utilizing BIM, clash detection can be carried out effectively and efficiently, thereby preventing additional costs due to on-site corrections. The aim of this research is to analyze the Cost Benefit Ratio achieved by using BIM in the construction of the MAKO BRIMOB and SPN Polda buildings in North Sulawesi. The research employs a quantitative method. The results indicate that the Benefit Cost Ratio for the MAKO Brimob and SPN Polda North Sulawesi project is 5.33, meaning that the benefits of the project outweigh the costs incurred. Therefore, the use of BIM can lead to greater cost efficiency.